Reading comprehension of mathematical problems and narrative and expository texts: an eye-tracking study - Pereira , Francine Baranoski; Klein, Angela Ines; Szmoski , Romeu Miqueias; Pereira, Ana Lucia (Cadernos do IL, 2024)
This research investigated reading comprehension of mathematical problems of students with better and worse performance in reading, called as effective and ineffective, being this performance measured by reading and comprehension tests of narrative and expository texts and by the average school performance in the subject Portuguese Language. 30 students read and mentally calculated six math problems, while their eye movements were recorded. Analyzes have shown that effective readers read in less time, made fewer fixations and saccades compared to ineffective readers. The results indicate that the worst performance in solving mathematical problems is attributed to the inability in reading and comprehension, and it was concluded that the good performance in reading and comprehension enables the acquisition of knowledge in all areas.